Manuel Seoane and Luis Heysen: Avatars of the Peruvian reformist style in Argentina in the 1920s - Bergel, Martín (2006)
In recent years, historiography has been concerned with illuminating various dimensions of the material plot that gave rise to that unique "Latin American moment" of the culture and politics of the continent, which takes place in the cycle that begins at the beginning of the century XX and accelerated from the University Reform of 1918. Even today -in times of globalization of culture and vertiginous contacts through the channels offered by new information technologies- the intensity of the links established in the early decades of the century by various Latin American intellectuals and cultural and political formations.